Cutaneous reactions due to antihypertensive drugs - Upadhayai J; Nangia Anup; Mukhija R; Misra Mukum; Mohan Lalit; Singh K (Wolters Kluwer Medknow Publications, 2006)
Out of a total of 1147 patients on antihypertensive drugs, 23 (2.04%) developed adverse cutaneous drug reactions (ACDR). The commonest antihypertensive drug group causing ACDR was beta-blockers of which atenolol was the commonest culprit. The second most common group was calcium channel blockers with amlodipine as the commonest offender. The most common patterns of ACDR observed included urticaria followed by lichenoid drug eruption (LDE). We noted 2 new patterns of reactions; (i) one patient developed brownish blue pigmentation of nails while on atenolol for 3 years, which resolved in 4 months after withdrawal and (ii) another patient on amlodipine for 8 years developed Schamberg′s like purpuric pigmentation, which resolved on withdrawal of drug within 3 months. These findings have not been reported in the literature earlier. This study is presented for paucity of Indian data on ACDR due to antihypertensive drugs, and remarkable advancement in area of cardiovascular and antihypertensive pharmacology and a large number of population taking antihypertensive drugs.